DAMPAK EVENT MASJID AL-AKBAR SURABAYA TERHADAP KESEJAHTERAAN PEDAGANG SEKITAR - Azizah, Nurul; Fahrullah, A'rasi (Jurnal Ekonomika dan Bisnis Islam, 2020)
Islamic tourism is a type of tourism that potentially has brought welfare for people. As an example, Al-Akbar Surabaya Mosque, which has various kinds of activities bringing the prosperity for vendors surrounding. This research aimed to determine how the impact of the event held by Al-Akbar's mosque towards the welfare of vendors surrounding. This research used a qualitative method with a descriptive approach. This research used the qualitative method using descriptives analysis techniques after doing the interview. Based on the result, the impact of welfare felt by the vendors. The existence of routine events organized by this mosque influenced the income and well-being of traders and their families. The effect perceived by the merchants both materially and spiritually has fulfilled the 'Maqasyid Syariah', proofed that the Al Akbar Mosque has fulfilled the concept of Islamic tourism which is to bring prosperity to the Ummah